Nanotechnology to the Rescue: Treatment Perspective for the Immune Dysregulation Observed in COVID-19 - Peter, Angela E.; Sandeep, B. V.; Rao, B. Ganga; Kalpana, V. Lakshmi (Frontiers in Nanotechnology, 2021)
The study of the use of nanotechnology for drug delivery has been extensive. Nanomedical approaches for therapeutics; drug delivery in particular is superior to conventional methods in that it allows for controlled targeted delivery and release, higher stability, extended circulation time, minimal side-effects, and improved pharmacokinetic clearance (of the drug) form the body, to name a few. The magnitude of COVID-19, the current ongoing pandemic has been severe; it has caused widespread the loss of human life. In individuals with severe COVID-19, immune dysregulation and a rampant state of hyperinflammation is observed. This kind of an immunopathological response is detrimental and results in rapid disease progression, development of secondary infections, sepsis and can be fatal. Several studies have pin-pointed the reason for this immune dysregulation; deviations in the signaling pathways involved in the mediation and control of immune responses. In severe COVID-19 patients, many signaling cascades including JAK/STAT, NF-κB, MAPK/ERK, TGF beta, VEGF, and Notch signaling were found to be either upregulated or inactivated. Targeting these aberrant signaling pathways in conjunction with antiviral therapy will effectuate mitigation of the hyperinflammation, hypercytokinemia, and promote faster recovery. The science of the use of nanocarriers as delivery agents to modulate these signaling pathways is not new; it has already been explored for other inflammatory diseases and in particular, cancer therapy. Numerous studies have evaluated the efficacy and potential of nanomedical approaches to modulate these signaling pathways and have been met with positive results. A treatment regime, that includes nanotherapeutics and antiviral therapies will prove effective and holds great promise for the successful treatment of COVID-19. In this article, we review different nanomedical approaches already studied for targeting aberrant signaling pathways, the host immune response to SARS-CoV-2, immunopathology and the dysregulated signaling pathways observed in severe COVID-19 and the current treatment methods in use for targeting signaling cascades in COVID-19. We then conclude by suggesting that the use of nanomedical drug delivery systems for targeting signaling pathways can be extended to effectively target the aberrant signaling pathways in COVID-19 for best treatment results.